Formation and application of hydrogen in non-ferrous metallurgy - Stopić, Srećko R.; Friedrich, Bernd G. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: Hydrogen is the most abundant element in the universe (75 % by mass) and the lightest element (with a density of 0.00082 g/cm3) which consists of only one proton and one electron. Because of its presence in many different forms such as gaseous hydrogen, its plasma species, water, acid, alkalline, ammmonia and hydrocarbons, it has various applications in different industrial disciplines. Methods: Different hydrometallurgical and pyrometallurgical methods are considered in order to point out many different processes such as formation of hydrogen, reduction of metallic oxides and chlorides, and electrochemical reactions such as hydrogen overvoltage and the spillover effect. Ultrasonic spray pyrolysis enables the formation of very fine aerosols which can be used for the production of metallic powders. Results: Hydrogen formation was observed during the dissolution of metallic allloys with hydrochloric acid. The reduction of metallic oxides and metallic chlorides by hydrogen leads to the formation of metallic powders. Metallic powders were collected by a new developed electrostatic precipitator. Conclusion: Hydrogen can be applied in different reduction processes for the production of metallic powders. Recycling processes can be used for the formation of hydrogen. A new research strategy for powder production is proposed combining recycling of the black mass of used Li-Ion batteries, ultrasonic spray pyrolysis, and hydrogen reduction.